1996
DOI: 10.1007/bf00403962
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adrenalectomy on the development of a pancreatic islet lesion in fa/fa rats

Abstract: Summary Adrenalectomy prevents development of obesity and hyperinsulinaemia in obese (fa/fa)Zucker rats, thereby implicating the hypothalamopituitary-adrenal axis in the pathogenesis of obesity. In this study glucose-induced insulin secretion and glucokinase activity were investigated in isolated islets from adrenalectomized and control obese and lean female rats. Islets from control fa/fa rats were more sensitive to glucose with a half-maximal effective concentration (ECs0) of 6.1 + 2.0 mmol. 1-1 compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…However, it becomes more difficult to reconcile an increase in ␤-cell UCP2 with the fasting hyperinsulinemia observed in obese and obese-diabetic rodents such as fa/fa and ZDF rats. This hypersecretion of insulin has been shown to be dependent on mitochondrial ATP production and K ATP channel inactivation (57) and may be related to altered kinetics of glucokinase or other metabolic enzymes (58), which strongly depends on the deranged hypothalamopituitary-adrenal axis in genetically obese rodent models (59). The increase in overall metabolism is sufficient to induce K ATP channel closure at lower than normal glucose (60).…”
Section: Ucp2 and Type 2 Diabetesmentioning
confidence: 99%
“…However, it becomes more difficult to reconcile an increase in ␤-cell UCP2 with the fasting hyperinsulinemia observed in obese and obese-diabetic rodents such as fa/fa and ZDF rats. This hypersecretion of insulin has been shown to be dependent on mitochondrial ATP production and K ATP channel inactivation (57) and may be related to altered kinetics of glucokinase or other metabolic enzymes (58), which strongly depends on the deranged hypothalamopituitary-adrenal axis in genetically obese rodent models (59). The increase in overall metabolism is sufficient to induce K ATP channel closure at lower than normal glucose (60).…”
Section: Ucp2 and Type 2 Diabetesmentioning
confidence: 99%
“…and tap water ad libitum prior to surgery. Rats were either bilaterally adrenalectomized (ADX) or sham-operated (SH) through a ventral incision after anesthesia with a mixture 2 mL of sodium pentobarbital (65 mg/ ml) and 2 mL diazepam (5 mg/mL) in 6 mL of saline (0.9% NaCl) (Kibenge and Chan 1996). After surgery the animals were housed individually, in an artificially lit room with a 12 h dark : light cycle at a temperature of 22-25°C.…”
Section: Animalsmentioning
confidence: 99%
“…Mannoheptulose (1-100 mM) was added to islet samples in media containing 16.5 mM glucose and all samples were then statically incubated for 90 min at 37°C (95% air-5% CO 2 , saturated with water vapour). Although culture conditions may alter insulin secretion patterns, our previous work demonstrated that the effects of ADX persisted in 24 h cultured islets (Kibenge and Chan 1996). Insulin release and islet insulin content were measured as previously described by Chan et al (1993).…”
Section: Islet Isolation and Insulin Releasementioning
confidence: 99%
See 2 more Smart Citations